Riverine networks constrain β‐diversity patterns among fish assemblages in a large Neotropical river. (5th August 2016) - Vitorino Júnior, Oscar B.; Fernandes, Rodrigo; Agostinho, Carlos S.; Pelicice, Fernando M.
Summary: Riverine metacommunities have been studied mainly in streams and headwaters, and little is known about how dendritic networks affect metacommunity structure in large river systems. We, therefore, examined fish assemblages in the Upper Tocantins River, Amazon Basin, to investigate the hypothesis that riverine networks constrain metacommunity structure. In particular, we investigated (i) taxonomic and functional β‐diversity along the river channel (main stem) and major tributaries (branches); (ii) the relative importance of the turnover and nestedness components; and (iii) the relationship between β‐diversity and spatial structure (the distance decay of similarity). Fish assemblages were sampled over a year (2007–2008) at 17 sites distributed along the main stem ( n = 8) and branches ( n = 9). We recorded 170 fish species in the 100‐km river section studied. Local species richness ranged from 45 to 79, with higher mean values in the main stem; local assemblages, however, showed high functional richness, with no significant difference between the main stem and branches. We observed that the turnover component contributed 87.7% of the variation in taxonomic β‐diversity (Jaccard), while the nestedness‐resultant contributed 12.3%. Taxonomic β‐diversity was on average 2.5 times higher than functional diversity, and taxonomic turnover was on average four times greater than functional turnover. In addition, a null model showed that observed values of functional β‐diversity were not different from random expectations, given the observed level of taxonomic β‐diversity. Branches showed higher species turnover, while significant distance decay of similarity was observed only along the main stem. Functional β‐diversity was not different between the main stem and branches and did not correlate with watercourse distance. Our study revealed that fish metacommunity in this large river shows species turnover, but with high functional similarity. In addition, different β‐diversity patterns between the main stem and branches indicate that the dendritic network constrained metacommunity structure. Mass effects and dispersal limitations probably explain β‐diversity patterns in the main stem, while a combination of mechanisms (i.e., disturbance, specific biological functions and dispersal constraints) affect diversity in the branches.